Putative Breast Cancer Driver Mutations in TBX3 Cause Impaired Transcriptional Repression - Fischer, Kathrin; Pflugfelder, Gert O. (Frontiers in Oncology, 2015)
The closely related T-box transcription factors TBX2 and TBX3 are frequently overexpressed in melanoma and various types of human cancers, in particular, breast cancer. The overexpression of TBX2 and TBX3 can have several cellular effects, among them suppression of senescence, promotion of epithelial–mesenchymal transition, and invasive cell motility. In contrast, loss of function of TBX3 and most other human T-box genes causes developmental haploinsufficiency syndromes. Stephens and colleagues (1), by exome sequencing of breast tumor samples, identified five different mutations in TBX3, all affecting the DNA-binding T-domain. One in-frame deletion of a single amino acid, p.N212delN, was observed twice. Due to the clustering of these mutations to the T-domain and for statistical reasons, TBX3 was inferred to be a driver gene in breast cancer. Since mutations in the T-domain generally cause loss of function and because the tumorigenic action of TBX3 has generally been attributed to overexpression, we determined whether the putative driver mutations had loss- or gain-of-function properties. We tested two in-frame deletions, one missense, and one frameshift mutant protein for DNA-binding in vitro, and for target gene repression in cell culture. In addition, we performed an in silico analysis of somatic TBX mutations in breast cancer, collected in The Cancer Genome Atlas (TCGA). Both the experimental and the in silico analysis indicate that the observed mutations predominantly cause loss of TBX3 function.